Dissociative Identity Disorder (DID) in Split’s Film by Night Shyamalan - diana rozelin; arif hidayat (English Language, Linguistics, Literature, And Education Journal, 2019)
This thesis analyzes Kevin's Dissociative Identity Disorder (DID) as seen in Night Shyamalan's Split film. The writer is interested in analyzing this film because the nature and character of Kevin as the main role is always changing, ranging from little children, adult men and women. This research was designed to determine the forms of Dissociative Identity Disorder (DID) and causes of Dissociative Identity Disorder (DID) and the solve Dissociative Identity Disorder (DID) by Kevin in the Split film by Night Shyamalan. The writer uses Dissociative Identity Disorder (DID) Theory by Nevid to support the writing of this thesis. This study uses qualitative research and descriptive method, analyzed and described in the form of words rather than numerical scores or statistics. The data of the research are the pictures and dialogue, which contains body language expressed by the main character. The research result shows that first, there are 4 forms of Dissociative Identity Disorder (DID) Kevin experienced were the main personality, where Kevin was the main personality, the dominant personality, the dominant personality in Kevin was personality became Dennis, dissociative identity disorder was not aware of each other, where Hedwig's personality was confused about what Dennis had done as an evil personality figure in Kevin, dissociative identity disorder competed to gain self-control of the perpetrators, often Dennis and Patricia took over Kevin. Second, there are 2 causes of Dissociative Identity Disorder (DID) that occur to Kevin, namely, experiencing severe childhood pain such as physical torture and sexual abuse, where Kevin always gets beaten from his own mother and sexual abuse from his uncle, encouraging himself to stand wild, Kevin who gets treatment is not good at trying to fight and not be yourself. Third, there are two ways when Kevin wants to solve Dissociative Identity Disorder (DID) in Night Shyamalan's Split Film, they get speech and Psychotherapy, where he meets a doctor if he always feels his past and the doctor asks him to forget his past and get a lot of talk, where he tries tell his thoughts.